Cytoplasmic tail-dependent internalization of membrane-type 1 matrix metalloproteinase is important for its invasion-promoting activity. - Uekita, T; Itoh, Y; Yana, I; Ohno, H; Seiki, M (2001)
Membrane-type 1 matrix metalloproteinase (MT1-MMP) is an integral membrane proteinase that degrades the pericellular extracellular matrix (ECM) and is expressed in many migratory cells, including invasive cancer cells. MT1-MMP has been shown to localize at the migration edge and to promote cell migration; however, it is not clear how the enzyme is regulated during the migration process. Here, we report that MT1-MMP is internalized from the surface and that this event depends on the sequence of its cytoplasmic tail. Di-leucine (Leu571-572 and Leu578-579) and tyrosine573 residues are important for the internalization, and the mu2 subunit of adaptor protein 2, a component of clathrin-coated pits for membrane protein internalization, was found to bind to the LLY573 sequence. MT1-MMP was internalized predominantly at the adherent edge and was found to colocalize with clathrin-coated vesicles. The mutations that disturb internalization caused accumulation of the enzyme at the adherent edge, though the net proteolytic activity was not affected much. Interestingly, whereas expression of MT1-MMP enhances cell migration and invasion, the internalization-defective mutants failed to promote either activity. These data indicate that dynamic turnover of MT1-MMP at the migration edge by internalization is important for proper enzyme function during cell migration and invasion.